2023
DOI: 10.1177/0734242x231155097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the household solid waste mandatory sorting policy in Shanghai: A 1-year public opinion survey

Abstract: Sustainable management of household solid waste (HSW) is an essential step in realizing the development of a circular economy (CE). However, for many developing countries, HSW sorting is evolving incrementally, and focusing on the intervention role of policy and the sorting behaviour of residents can help achieve sustainable waste management. This study aims to investigate the main determinants of residents’ HSW sorting behaviour and how policy particularly contributes to it. Drawing upon the theory of planned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Mandatory waste separation policies are important for activating public participation in waste separation (Chen et al, 2022). Empirical studies have confirmed the success of mandatory waste separation policy in Shanghai, which is the garbage classification pilot city in China (Liu et al, 2023;Wang et al, 2021), and it is found that mandatory waste separation policies can promote residents' willingness of waste separation (Li et al, 2020a). Therefore, the research hypothesis H2 is proposed.…”
Section: Command-control Policy Toolsmentioning
confidence: 94%
See 1 more Smart Citation
“…Mandatory waste separation policies are important for activating public participation in waste separation (Chen et al, 2022). Empirical studies have confirmed the success of mandatory waste separation policy in Shanghai, which is the garbage classification pilot city in China (Liu et al, 2023;Wang et al, 2021), and it is found that mandatory waste separation policies can promote residents' willingness of waste separation (Li et al, 2020a). Therefore, the research hypothesis H2 is proposed.…”
Section: Command-control Policy Toolsmentioning
confidence: 94%
“…Existing literature of residents' WSB usually focus on the individual influencing factors with the planned behaviour theory to explore the determinants of WSB, including attitudes, subjective norms and perceived behaviour control (Hu et al, 2021;Liu et al, 2023;Wang et al, 2020b). The habitual factor referred as the previous behaviours or habits is an important factor affecting waste sorting behaviour (Pakpour et al, 2014;Tang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…By implementing comprehensive policy measures, such as landfill bans, landfill taxes, and deposit refund schemes, these countries have been able to divert waste from landfills and incineration towards energy recovery and recycling [19]. The success of recycling policies also depends on factors such as the initial establishment of recycling facilities, pilot city initiatives, and per capita GDP [20]. Overall, recycling policies play a crucial role in shaping waste management practices and can contribute to the development of a sustainable and circular economy [21].…”
Section: Recycling Policymentioning
confidence: 99%
“…According to TPB, behavioral attitudes, subjective norms, and perceived behavioral control, all have an impact on a person's purpose [ 11 ]. Within the TPB's framework, several scholars have investigated the WSB of residents in different regions of China and concluded that subjective norms, attitudes, and perceived behavioral control all promote the generation of residents' intention to sort waste [ 4 , 10 , 12 ], but some scholars believe that subjective norms have a negative influence [ 7 ]. Numerous research has demonstrated the feasibility of the TPB for predicting WSB [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%